RANCANG BANGUN TIMER DAN WATER LEVEL SENSOR PADA ALAT NEBULIZER BERBASIS ARDUINO UNO - Nasution, Muhammad Ananda Rifky; Dabukke, Hotromasari; Primasyukra, Mhd.Aldi (JURNAL MUTIARA ELEKTROMEDIK, 2023)
A nebulizer is a piece of equipment used to convert liquid medication into an aerosol that will be inhaled by the user according to a doctor's prescription. The design of a timer and water level sensor on an Arduino Uno-based nebulizer was carried out to make it easier for users to operate and add an automation system that is integrated with an Arduino Uno type microcontroller. This design has the same device concept as a nebulizer in general, but adds a timer system via an attached push button and relay. Apart from that, the addition of a water level sensor is used to detect the amount of fluid in the reservoir. This design uses an experimental concept with narrative qualitative research methods. Device design is divided into 2 types, namely hardware and software. Programming using Arduino IDE and circuit simulation using Proteus. The design was successfully made and testing was carried out on the timer and water level sensor. The nebulizer worked according to its function and the timer test error value was 0.018704323 with a comparison difference with the stopwatch of 0.5 seconds.